Komunikasi Pemasaran Terpadu dan Ekuitas Merek Gojek Indonesia Cabang Yogyakarta - Novia Tri Lestari; Hani Sirine (Faculty of Economic and Business, 2019)
Companies that are able to communicate their marketing will have an impact on brand equity improvement. This study aims to examine the influence of Integrated Marketing Communications (IMC) which consists of advertising, personal selling, sales promotion, public relations and publicity, direct marketing, instructional materials and corporate design to the brand equity of Gojek Yogyakarta. The sample of this study amounted 150 respondents who are Go-Ride customers who already know IMC Gojek. The analysis technique used is multiple linear regression. The results showed that IMC influence brand equity, and partially variable of advertising, sales promotion, and corporate design having significant positive effect to brand equity. Based on the results of this study, Gojek Yogyakarta needs to increase the promotion of ideas to change attitudes and consumer behavior, increase the value of the product so as to achieve certain marketing goals, and strengthen the picture of service outlet or corporate identity for the message received by consumers through effective marketing communication channel mix.